2012
DOI: 10.1017/s1041610212000774
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attitudes to aging and physical and mental health in older adults

Abstract: The promotion of successful aging is increasingly becoming important in aging societies. Having positive attitudes to aging may contribute to healthier mental and physical outcomes in older adults. Overcoming negative stereotypes of aging through change at the societal and individual level may help to promote more successful aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
187
4
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(252 citation statements)
references
References 30 publications
(34 reference statements)
39
187
4
7
Order By: Relevance
“…Two crosssectional studies have pointed to the link between more positive attitudes toward ageing and less depression (Bryant et al 2012), which has also been found in relation to subsyndromal depressive symptoms (Chachamovich et al 2008). Moreover, a recent study of over 2000 older military veterans in the U.S. has found that those who had more negative stereotypical perceptions of their own ageing, reported a higher frequency of psychiatric symptoms, in comparison with those who had fewer negative stereotypical perceptions of ageing (Levy et al 2014).…”
Section: Self-ageism Among Older Patients With Mental Illnessmentioning
confidence: 95%
“…Two crosssectional studies have pointed to the link between more positive attitudes toward ageing and less depression (Bryant et al 2012), which has also been found in relation to subsyndromal depressive symptoms (Chachamovich et al 2008). Moreover, a recent study of over 2000 older military veterans in the U.S. has found that those who had more negative stereotypical perceptions of their own ageing, reported a higher frequency of psychiatric symptoms, in comparison with those who had fewer negative stereotypical perceptions of ageing (Levy et al 2014).…”
Section: Self-ageism Among Older Patients With Mental Illnessmentioning
confidence: 95%
“…When factors are highly correlated, they will inevitably relate to external constructs in less discrete ways, so the unique contribution of each factor is more difficult to identify. Because attitudes to ageing are highly relevant to health and well-being [3,4], better articulated factors enable a more precise identification of which subscales underlie these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The physical change and psychological growth domains are positively worded with higher scores indicating more positive attitudes, whereas the psychosocial loss scale is negatively worded, with higher scores indicating a more negative attitude. Following Bryant and colleagues' protocol [3], we defined mean subscale scores > 3 for psychological growth and physical loss, and <3 for psychosocial loss, as indicating a positive attitude to ageing, with the remaining range indicating a negative attitude on the respective subscale.…”
Section: The Attitudes To Ageing Questionnaire (Aaq)mentioning
confidence: 99%
See 2 more Smart Citations